Perbandingan Produktivitas Blasting Menggunakan Copper Slag Baru, 1 & 2 Pada Permukaan Kapal dengan Preparation Spot Sweep Menggunakan Metode ANOVA - Kerans, Sisilia S Lelo; Putri, Erni Puspanantasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Dry abrasive blasting is a critical process in the shipyard industry for removing rust and contaminants from steel surfaces prior to coating. Copper slag, a by-product of copper smelting, is commonly used as an abrasive medium due to its hardness. This study compares blasting productivity using new copper slag, first-cycle recycled copper slag, and second-cycle recycled copper slag. The evaluated parameters include processing time, cleaned surface area, and surface roughness. A quantitative method employing one-way Analysis of Variance (ANOVA) was applied to determine significant differences among the treatments. The results show that new copper slag produces the highest surface roughness but requires longer processing time. First-cycle recycled copper slag provides the most optimal balance between time efficiency and surface quality, while second-cycle recycled copper slag achieves the fastest processing time with reduced surface roughness. ANOVA results indicate significant differences among the three treatments. The findings suggest that copper slag can be effectively reused for one recycling cycle without compromising the Sa 2.5 standard according to ISO 8501-1.